1985
DOI: 10.1172/jci112166
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic concentrations of glucocorticoids suppress the antimicrobial activity of human macrophages without impairing their responsiveness to gamma interferon.

Abstract: By exposing human blood-derived macrophages and alveolar macrophages in vitro to dexamethasone, we showed in these studies that glucocorticoids markedly suppress the antimicrobial activity of macrophages but not macrophage activation by lymphokines. As little as 2.5 X 10-8 mol/liter of dexamethasone prevented macrophages from inhibiting germination of Aspergillus spores or from eliminating ingested bacteria such as Listeria, Nocardia, or Salmonella. Damage to macrophage function was inhibited by progesterone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
1
4

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(139 citation statements)
references
References 31 publications
9
125
1
4
Order By: Relevance
“…Indeed, a number of macrophage responses to IFN-␥ are not inhibited by glucocorticoids. IFN-␥ upregulation of Fc-R in human monocytes is enhanced by Dex (41,42), therapeutic concentrations of glucocorticoids have been shown to suppress the antimicrobial activity of human macrophages without impairing their responsiveness to IFN-␥ (43,44), and IFN-␥-induced macrophage antibody-dependent cellular cytotoxicity is not inhibited by Dex (45). In our studies, Dex inhibited the ability of IFN-␥-activated macrophages to accumulate within the glomerulus and thus prevented renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of macrophage responses to IFN-␥ are not inhibited by glucocorticoids. IFN-␥ upregulation of Fc-R in human monocytes is enhanced by Dex (41,42), therapeutic concentrations of glucocorticoids have been shown to suppress the antimicrobial activity of human macrophages without impairing their responsiveness to IFN-␥ (43,44), and IFN-␥-induced macrophage antibody-dependent cellular cytotoxicity is not inhibited by Dex (45). In our studies, Dex inhibited the ability of IFN-␥-activated macrophages to accumulate within the glomerulus and thus prevented renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Resident alveolar macrophages ingest and kill resting conidia, largely through nonoxidative mechanisms, while neutrophils use oxygen-dependent mechanisms to attack hyphae germinating from conidia that escape macrophage surveillance (13,14). The effectiveness of this system is evident from the observation that challenge with even large numbers of conidia fails to cause disease in immunocompetent animals (17), and recognized major risk factors in humans are defects in phagocyte functions, such as those occurring in chronic granulomatous disease (18,19), cortisone-induced suppression of macrophage conidiocidal activity (20,21), and chemotherapy-induced neutropenia (22). Increased risk of a chronic form of IPA that is independent of neutropenia and corticosteroid therapy has been noticed in patients with HIV (8), who also showed a defective effector activity of neutrophils against A. fumigatus (23).…”
Section: T Cell Vaccination In Mice Withmentioning
confidence: 99%
“…In experimental animals, alveolar and peritoneal macrophages bind and engulf Aspergillus fumigatus conidia in vitro (10,(13)(14)(15) and produce IL-1 and TNF when exposed to either conidia or hyphae (16). In vitro studies of human peripheral monocytes (17,18), monocyte-derived macrophages (19), and alveolar macrophages (20,21) have also shown these cells to phagocytose conidia and kill both conidial and hyphal forms of A. fumigatus. One study has suggested a role for splenic macrophages in acquired immunity against i.v.…”
Section: Macrophage Inflammatory Protein-1␣ Is a Critical Mediator Ofmentioning
confidence: 99%